Ex post facto analysis of the Sedgwick Sand Draws Project: a case study of the small watershed program - Ward, Jason P., author; Ruff, James, advisor; Grigg, Neil, committee member; Wilkins-Wells, John, committee member (Colorado State University. Libraries, 1999)
The Sedgwick Sand Draws Project is a flood control project completed in 1992 to provide floodwater damage protection for agricultural and municipal lands in Sedgwick County, which lies in extreme northeastern Colorado along the South Platte River. Funding and technical support for the project was provided by the U.S. Soil Conservation Service (SCS) under the Watershed Protection and Flood Prevention Act, commonly referred to as The Small Watershed Program. Short duration, high intensity thunderstorms occur in mid to late summer in the upland portions of the Sand Draws Watershed near the Colorado- Nebraska border. Runoff from these storms is channeled into upland sand draws that drain into the developed alluvial floodplain below. Before project average annual floodwater damages were estimated at $220,050. An ex post facto method was proposed for evaluating the damage reduction benefits of a watershed flood control project. Using economic, hydrologic and engineering principles, damage-frequency curves developed in the proposal phase of a project are used to estimate actual damage reduction benefits. Estimates are made by adjusting the damage-frequency curves to reflect a current economic time base and evaluating damages produced by hydrologic events that have occurred during the period of analysis. Other performance indicators, such as site inspections, historical crop yields, changes in land use, disaster relief application rates, and interviews with local community members are also used in the evaluation. The ex post facto evaluation principles were applied to the Sand Draws project as a case study. However, lack of information in the SCS Sand Draws proposal required a technique for estimating the original damage-frequency curves. A method for estimating the curves from minimal known information was developed and used for the Sand Draws project. The period of analysis was from completion of the project in June 1992, to the latest date of available data, September 1997. Hydro logic analysis of the watershed identified seven damage producing rainfall events during this period. It was estimated that the project has produced a total of$3,556,628 in damage reduction benefits resulting in average annual benefits of $592,771. Benefit-cost analyses and a look at other performance indicators were also evaluated.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Flood control -- Colorado -- Sedgwick County; Flood damage prevention; Colorado -- Sedgwick County